2013
DOI: 10.1042/bj20130481
|View full text |Cite
|
Sign up to set email alerts
|

Flavanoids induce expression of the suppressor of cytokine signalling 3 (SOCS3) gene and suppress IL-6-activated signal transducer and activator of transcription 3 (STAT3) activation in vascular endothelial cells

Abstract: The atherogenic cytokine IL-6 (interleukin-6) induces pro-inflammatory gene expression in VECs (vascular endothelial cells) by activating the JAK (Janus kinase)/STAT3 (signal transducer and activator of transcription 3) signalling pathway, which is normally down-regulated by the STAT3-dependent induction of the E3 ubiquitin ligase component SOCS3 (suppressor of cytokine signalling 3). Novel treatments based on the regulation of SOCS3 protein levels could therefore have value in the treatment of diseases with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 48 publications
2
44
0
1
Order By: Relevance
“…However, AMPK is commonly linked with the NF-κB pathway to explain inflammation control27. Previously, naringenin was found to directly activate AMPK in vascular endothelial cells and muscle cells2829. Therefore, we speculated that naringenin may induce ATF3 upregulation by activating AMPK.…”
Section: Discussionmentioning
confidence: 95%
“…However, AMPK is commonly linked with the NF-κB pathway to explain inflammation control27. Previously, naringenin was found to directly activate AMPK in vascular endothelial cells and muscle cells2829. Therefore, we speculated that naringenin may induce ATF3 upregulation by activating AMPK.…”
Section: Discussionmentioning
confidence: 95%
“…Whereas other studies have showed different results regarding the effect of STAT activation on chemokine and cytokine secretion. In human umbilical vein endothelial cells, MCP-1 mRNA expression was dependent on STAT3 activation (Wiejak et al, 2013). According to our results, we suggest that STAT1 activation by IFN-β plays a key role in the pro-inflammatory response of cultured CF.…”
Section: Discussionmentioning
confidence: 99%
“…An additional time point of 6 h was performed for IL-10 treatments. For experiments assessing SOCS3 stabilization, THP-1 cells were pre-incubated with or without IL-10 (20 ng/ml) for 30 min before the addition of IL-6 (10 ng/ml) in the presence or absence of 10 μM of the proteasome inhibitor MG132 (Calbiochem, Merck Millipore) for 5 h. To verify the effects of MG132 in preventing the proteolytic degradation of newly synthesized SOCS3 by the ubiquitin–proteasome system (16) aditional experiments were performed in THP-1 cells pre-incubated in the absence or presence of MG132 (10 μM) for 30 min before the addition of IL-6 (10 ng/ml) for 5 h. In some experiments, LPS stimulation was performed in the presence of a mouse monoclonal anti-human IL-10 receptor (10 μg/ml) or control non-immune mouse immunoglobin (IgG) (R&D Systems). At the end of the incubation periods, cells and supernatants were collected for futher analysis.…”
Section: Methodsmentioning
confidence: 99%